Existential Feminism in Andrea Hirata’s Novel Padang Bulan and Cinta Di Dalam Gelas - Suhadi, Muhammad Fatih; Pardi, Pardi; Manugeren, M; Zein, T Thyrhaya; Pratiwy, Devi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Gender issues have remained a hot issue owing to various influencing factors, including gender overlap and social inequality. Gender is a social sex reconstructed by society for both men and women. The gender difference stereotypes have given rise to gender injustice detrimental to women. The presence of the concept of existential feminism initiated by Simone De Beauvoir is a bright spot and hope for all women, especially those in patriarchal system communities. The purpose of this research is to uncover the traditional paradigm that women are cultural products and their independence is delimited. This is not in accordance with the concept of human rights which basically states that every human being has the same rights in carrying out life. So it is hoped that this paper can be used as a reference to eliminate the marginalization of women. The research is carried out using a qualitative descriptive design with phenomenological method to explore or photograph social situations thoroughly, broadly and deeply and also supported by the theory of sociology of literature, the description of social reality in literary works. The data collection procedures and the data analysis are done systematically based on the existing theories of qualitative research method. The results of the research show that the protagonist implements the existential feminist concept through the ability to work, being intellectual and responsible.  Throughout the research it is proved that existential feminism still exists to explore the marginalization of woman, summed up with a text that women are independent beings. Keywords: Existential Feminism, Intellect, Profession, Responsibility